Bias‐Dependent Stability of Perovskite Solar Cells Studied Using Natural and Concentrated Sunlight. Issue 2 (15th October 2019) - K. M., Anoop; Khenkin, Mark V.; Di Giacomo, Francesco; Galagan, Yulia; Rahmany, Stav; Etgar, Lioz; Katz, Eugene A.; Visoly-Fisher, Iris
Abstract : Degradation rates in perovskite solar cells (PSCs) were previously shown to be bias dependent; however, little is known about the mechanisms and driving factors that account for such degradation. Herein, stability studies under concentrated sunlight are demonstrated as a powerful experimental methodology to investigate bias‐dependent PSC degradation mechanisms. Stress testing of encapsulated PSCs' stability shows that light intensity is more significant than the illumination dose for PSC degradation under short‐circuit (SC) conditions, whereas the dose is the determining factor under open‐circuit (OC) stressing. This indicates that different degradation mechanisms are dominant under different bias conditions. It is postulated that degradation at SC biasing is dominated by ion migration, facilitated by photogenerated defects. Degradation at OC biasing can be explained by photogenerated radicals acting as nonradiative recombination centers (charge traps), which are created via reactions with accumulated charge carriers. Trap formation upon OC biasing is in accordance with degradation of photoluminescence and OC voltage ( V OC ) observed under this stress. A combination of multiple mechanisms, all with reduced driving forces compared with OC /SC biasing, explains degradation at maximum power point biasing. Understanding the bias effect on PSC stability can elucidate the underlying degradation mechanisms and lead to routes to reduce them. Abstract : Perovskite solar cells suffer from limited long‐term stability, which is currently an obstacle for using them for efficient solar energy conversion. Bias‐dependent degradation mechanisms in perovskite solar cells are studied utilizing concentrated natural sunlight, revealing different dominant mechanisms under different bias conditions. Understanding the degradation mechanism(s) dominant at the cell's operating conditions yields routes to eliminate or reduce them.